Crafting a Path to Retirement: Exploring the Link Between Subjective Age, Job Crafting, and Age-Inclusive Practices - Die, Kalvaince (East Carolina University)
As the American workforce ages, organizations must navigate the complexities of managing the widest age span the U.S. workforce has ever seen, presenting challenges and opportunities for HR managers seeking to motivate and retain workers. While chronological age explains some differences in work motivation, subjective age offers a deeper, more flexible understanding of employees’ experiences. This study examined how subjective age shapes approach and avoidance crafting behaviors, retirement intentions, and perceived financial preparedness, as well as how age-inclusive HR practices (AIHRP) moderate these relationships. Data were collected from 437 full-time U.S. workers. Findings revealed that subjective age positively predicted avoidance crafting and retirement intentions, suggesting that older-feeling workers are more inclined toward disengagement and transition out of the workforce. Avoidance crafting was positively related to perceived financial preparedness, while approach crafting was negatively related to retirement intentions, indicating that proactive work engagement may reduce intentions to retire. Notably, AIHRP moderated the relationship between subjective age and avoidance crafting, indicating that age-inclusive organizational practices can shape individual employee behavior. These findings highlight the importance of designing HR practices that address subjective age experiences to promote productive and satisfying late-career work trajectories. From an applied perspective, the positive relationship between subjective age and avoidance crafting underscores the need for organizations to address how employees’ internalized age perceptions shape their work behaviors. Notably, the study’s models examined whether subjective age predicts outcomes above and beyond established individual differences and emotional attachment to one’s organization. Affective commitment, psychological capital, and core self-evaluations emerged as the strongest predictors of crafting types and perceived financial preparedness. This suggests that age-inclusive HR practices alone may not suffice; companies may achieve better outcomes by pairing them with targeted efforts to strengthen employees’ psychological resources through training exercises. Simultaneously, organizational leaders are responsible for maintaining a supportive work environment and a positive organizational climate to reinforce and amplify the benefits of AIHRP. Moreover, the results emphasize that AIHRP are not universally beneficial; their effectiveness depends in part on individual differences such as subjective age. Consistent with the theory of aged heterogeneity, older workers cannot be treated as a monolith, given their diverse needs, preferences, and motivations. For example, older-feeling employees may respond to AIHRP with disengagement or withdrawal behaviors if their work is not sufficiently meaningful or well-matched to their goals. Managers and leaders must therefore proactively adjust tasks, reallocate workloads, and emphasize the value and significance of work to create a more emotionally meaningful experience. Finally, by distinguishing approach and avoidance crafting as separate behavioral patterns, organizations can better target interventions: promoting approach crafting may help delay retirement intentions, while identifying and addressing avoidance crafting may be critical to reducing turnover risk and supporting sustainable, satisfying late-career trajectories.
Keywords: Psychology, Behavioral Sciences